2020
DOI: 10.3390/robotics9020034
|View full text |Cite
|
Sign up to set email alerts
|

The Use of UTAUT and Post Acceptance Models to Investigate the Attitude towards a Telepresence Robot in an Educational Setting

Abstract: (1) Background: in the last decade, various investigations into the field of robotics have created several opportunities for further innovation to be possible in student education. However, despite scientific evidence, there is still strong scepticism surrounding the use of robots in some social fields, such as personal care and education. (2) Methods: in this research, we present a new tool named the HANCON model, which was developed merging and extending the constructs of two solid and proven models—the Unif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 55 publications
5
33
0
Order By: Relevance
“…Welch and colleagues (2020) noted that the UTAUT model constructs are significant determinants of behavioral intention to use Mobile Learning and found age and gender moderate the relationship between the UTAUT constructs. Han and Conti (2020) concluded that UTAUT and PAM models' emerge constructs could predict and explain social telepresence robots' acceptance in social contexts. Therefore, computer self-efficacy has a positive impact on perceived ease of use (PEOU), but (PEOU) has no significant effect on students' attitudes (Ho et al 2020).…”
Section: Conceptual Framework and Literature Reviewmentioning
confidence: 99%
“…Welch and colleagues (2020) noted that the UTAUT model constructs are significant determinants of behavioral intention to use Mobile Learning and found age and gender moderate the relationship between the UTAUT constructs. Han and Conti (2020) concluded that UTAUT and PAM models' emerge constructs could predict and explain social telepresence robots' acceptance in social contexts. Therefore, computer self-efficacy has a positive impact on perceived ease of use (PEOU), but (PEOU) has no significant effect on students' attitudes (Ho et al 2020).…”
Section: Conceptual Framework and Literature Reviewmentioning
confidence: 99%
“…conferencing methods. Han(Han & Conti, 2020) examined the attitude towards telepresence robots in the educational space by teachers. The Kubi robot was used in the experiment and 112 teachers participated.…”
mentioning
confidence: 99%
“…The previous studies explained that attitudes toward teaching assistance robots mainly determined teacher"s intended use for the robots [20], the highest positive effect was determined of attitude toward to intention of use of a Telepresence Robot in the classroom by teachers compared with other variables (perceived usefulness, perceived enjoyment, trust of technology, social influence, and gender) [47], it was in accordance with this study indicated that Lego Mindstorms Ev3 as learning tools were attractive, fun, and useful in the learning process had a positive influence on the behavioral intention of the teacher to use Lego Mindstorms in a lesson. www.ijacsa.thesai.org Furthermore, by emphasizing one of the social factors such as subjective norm, this study showed that organizations and other teachers supported to use of Lego Mindstorms Ev3 in the classroom, subjective norms have a positive correlation with PU, PE, and BI, this result consists to a previous study that one of important predictors in the robot acceptance model was subjective norm [48].…”
Section: Discussionmentioning
confidence: 99%